2009
DOI: 10.3171/2009.1.jns08499
|View full text |Cite
|
Sign up to set email alerts
|

The influence of focal brain cooling on neurophysiopathology: validation for clinical application

Abstract: The present study confirmed that the focal cooling of the cortex for 1 hour above the temperature of 0 degrees C did not induce any irreversible histological change or motor dysfunction. These results suggest that focal brain cooling above 0 degrees C has the potential to be a minimally invasive and valuable modality for the treatment of severe brain injury or to assist in the examination of brain function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 45 publications
1
33
0
Order By: Relevance
“…Histopathologic analysis of FBC has already been conducted in animal models at 5°C . The concentration of extracellular glycerol was measured as an indicator of structural damage to neurons and glia, since glycerol is derived from glycophospholipids in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathologic analysis of FBC has already been conducted in animal models at 5°C . The concentration of extracellular glycerol was measured as an indicator of structural damage to neurons and glia, since glycerol is derived from glycophospholipids in the cell membrane.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, focal brain cooling (FBC) has been proposed as a method for treating refractory epilepsy, which in turn has promoted the development of implantable focal cooling devices . The effect of cooling on epilepsy has been demonstrated in various animal experiments; these report that epileptic discharges (EDs) can be terminated by FBC . However, the precise influence of cooling on the molecular basis of epilepsy needs to be explored to obtain the benefits and to understand the possible risks that may be linked to this form of treatment.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A cooling device originally developed in our laboratory (Imoto et al., 2006; Oku et al., 2009; Fujioka et al., 2010) was used in the study. This device includes a cooling component and a heat‐processing component.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, we investigated the neuropathological consequences of focal cooling and changes in threshold temperature, which cause irreversible histological change in the neocortices of rats. 19) We concluded that focal cortical cooling at -59 C for 1 hour causes irreversible histological changes, which are coincident with the cryoinjury in the cooled cortex. However, focal brain cooling above 09 C for 1 hour did not cause motor dysfunction or histological damage (Fig.…”
Section: Influence Of Focal Cooling On Brain Tissuementioning
confidence: 99%